Antioxidant Activities of Ethanolic Extracts Obtained from α-Pinene-Containing Plants and Their Use in Cosmetic Emulsions - Jadwiga Grzeszczak; Agnieszka Wróblewska; Adam Klimowicz; Sylwia Gajewska; Łukasz Kucharski; Zvi C. Koren; Katarzyna Janda-Milczarek (MDPI AG, 2024)
α-Pinene is the bicyclic, unsaturated terpene hydrocarbon present in many plants. Due to its beneficial chemical properties, this compound is of great interest and has found numerous applications as a raw material in many chemical industries as well as in medicine and cosmetics. The aim of this study was to evaluate the antioxidant activities of ethanolic extracts obtained from plants containing α-pinene and to test the properties of cosmetic emulsions prepared with these extracts. The raw plant materials consisted of fresh parts of Pinus sylvestris L., such as cones, needles, and branches, as well as dried unground and ground pinecones; dried and fresh Rosmarinus officinalis leaves; dried Levisticum officinale leaves; and dried Salvia officinalis L. leaves. The plant materials were individually extracted with 40% (v/v), 70% (v/v), and 96% (v/v) ethanol using ultrasound-assisted extraction (UAE) for 15, 30, or 60 min. This method is a green extraction technique, frequently applied to isolate active substances from plants. For the selected plant materials, Soxhlet extraction with 96% (v/v) ethanol was also performed. The qualitative and quantitative analyses of the components in the selected extracts were performed with gas chromatography coupled with mass spectrometry (GC-MS). The antioxidant activities of the extracts were evaluated with the DPPH and ABTS methods. The extracts of three plant materials with the highest antioxidant activities-dried Rosmarinus officinalis leaves, dried Salvia officinalis L. leaves, and dried and ground Pinus sylvestris L. cones-were selected to be incorporated in cosmetic emulsions containing glyceryl monostearate and Olivem 1000 as emulsifiers. The stabilities and antioxidant activities of the emulsions were evaluated. Moreover, the antimicrobial properties of the emulsions using microbiological tests were also determined. The findings suggest that the prepared emulsions are stable cosmetic products with a high antioxidant potential.